Projeto e aplicação do design thinking em uma fazenda de aquicultura orgânica - Kafensztok, Márcia (2016)
PRIMAR is an organic aquaculture farm with a vocation for research and development (R & D) of innovative projects in estuarine aquaculture, with wide recognition of its projects at national and international level loses, with the death of its founder, the biologist responsible for R & D in company. PRIMAR employees, friends and family, take the management of the company and in return for services rendered to the Brazilian aquaculture for more than 20 years, several professionals offer their expertise in aquaculture to maintain the technological support necessary to continue the PRIMAR. To manage and continue the activities of the company, the new manager of PRIMAR, a professional designer, starts the application of her knowledge in the process of Design Thinking. Then starts a rescue of the knowledge produced in PRIMAR on aquaculture farming, its history, records, business plans, future projects and networking. With the cooperation of the employees and their knowledge of the historical of aquaculture farming, started a review of the control and recording formats, to the routine production procedures, while new communication processes were being built and incorporated. The visual communication projects are used as basic tools to support operational procedures. The three scientific manuscript that integrate the present descriptive memorandum, describe the processes, methodologies and results with the interference of the design. The generated solutions have been deployed and an internal survey of employees shows the contribution of design in communication between employees and understanding of the procedures of routines PRIMAR.